2015
DOI: 10.3390/nu7105435
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Fatigue Constituents of Okra

Abstract: Okra (Abelmoschus esculentus (L.) Moench), a healthy vegetable, is widely spread in tropical and subtropical areas. Previous studies have proven that okra pods possess anti-fatigue activity, and the aim of this research is to clarify the anti-fatigue constituents. To achieve this, we divided okra pods (OPD) into seeds (OSD) and skins (OSK), and compared the contents of total polysaccharides, total polyphenols, total flavonoids, isoquercitrin, and quercetin-3-O-gentiobiose and the antioxidant activity in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 43 publications
(50 reference statements)
7
109
1
Order By: Relevance
“…The mice in all the groups were subjected to the forced swimming test 30 min after the last administration. The test was carried out as previously described, with some modification . In brief, the mice were placed in an acrylic plastic pool (50 × 40 × 50 cm) filled with fresh water (25 ± 1 °C) to a depth of 30 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice in all the groups were subjected to the forced swimming test 30 min after the last administration. The test was carried out as previously described, with some modification . In brief, the mice were placed in an acrylic plastic pool (50 × 40 × 50 cm) filled with fresh water (25 ± 1 °C) to a depth of 30 cm.…”
Section: Methodsmentioning
confidence: 99%
“…The test was carried out as previously described, with some modification. 34 In brief, the mice were placed in an acrylic plastic pool (50 × 40 × 50 cm) filled with fresh water (25 ± 1°C) to a depth of 30 cm. Exhaustion was defined as loss of coordinated movements and failure to rise to the surface within 7 s, and the swimming time was recorded.…”
Section: Forced Swimming Testmentioning
confidence: 99%
“…Independence activity test was performed according to the method described previously with some modification [22]. Thirty minutes after AC administration, mice were placed individually in the autonomic activities instrument (ZZ-6, Chengdu Taimeng Science Technology Co., Ltd., Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant assays, including 1-diphenyl-2-picrylhydrazyl scavenging, ferric reducing antioxidant power, reducing power test and weight-loaded swimming test showed its seeds possessed significant antioxidant and antifatigue effects. Moreover, biochemical determination revealed that anti-fatigue activity of okra seeds is caused by reducing the levels of blood lactic acid and urea nitrogen, enhancing hepatic glycogen storage, promoting anti-oxidant ability by lowering malondialdehyde level and increasing superoxide dismutase and glutathione peroxides levels [37].…”
Section: Anti-fatigue and Anti-oxidant Effectsmentioning
confidence: 99%